GOVERNMENT POLICY REGARDING COAL AND NICKEL EXPORT BAN THE IMPACT ON THE INDONESIAN MINING INDUSTRY - Rivo Ardianti; Wuryaningsih Dwi Lestari (Jurnal Telekomunikasi dan Informatika, 2023)
Financial performance is a prospect for the company's financial growth. The company's financial performance will always be different in each company and each period. This study aims to analyze the effect of government policy regarding the ban on the export of coal and nickel in the form of raw materials on the company's financial performance by looking at the stock prices and sales of related companies. In this study, researchers used secondary data by processing data through eviews-12. The company's annual financial report data were obtained from www.idxchanel.com and stock price data obtained from id.investing.com. company's financial performance affects stock prices. The research results prove that government policies affect the company's financial performance and company's stock price. In this study it can be seen that the return on assets and debt ratios have an effect on stock prices while the current ratio has no effect on stock prices.